Antibiotic and Surgical Treatment of Diabetic Foot Osteomyelitis: The Histopathological Evidence - Roberto Da Ros; Roberta Assaloni; Andrea Michelli; Barbara Brunato; Cesare Miranda (Antibiotics)
Background: Osteomyelitis is one of the most frequent infections of the diabetic foot, accounting for 20–70% of foot infections. The treatment of osteomyelitis continues to be debated, and the possibility of performing conservative surgery associated with targeted antibiotic treatment allows for reductions in the amount of bone removed, the resolution of osteomyelitis, and a reduction in the changes in the biomechanics of the foot. The objective of this study was to evaluate the outcomes of osteomyelitis treatment with a combination of antibiotic and surgical procedures based on a histopathological analysis of the infected bone and margins. Materials and Methods: We analyzed 25 diabetic patients with osteomyelitis. We treated each patient with empiric antibiotic treatment, surgical removal of the infected bone, and targeted antibiotic treatment. During the surgical procedure, we collected infected bone samples and margins for microbiological and histopathological analyses. Results: All the patients had type 2 diabetes, with a mean age of 71 ± 10 years. Antibiotic therapy was administered orally for an average duration of 21 ± 9 days, aimed at improving the microbiological outcome. Histological examinations of the resected infected bone revealed the presence of osteomyelitis in 23 (92%) patients. The healthy margin sample, surgically assessed as non-infected, was confirmed negative in 80% of cases. At a follow-up of 18 ± 7 months, we achieved complete healing in twenty patients (80%), with an average healing time of 70 ± 41 days. No recurrence of osteomyelitis was observed. Conclusions: The data from this study demonstrate that the combination of targeted antibiotic therapy and conservative surgical treatment is effective in resolving osteomyelitis without recurrence with a very long follow-up. Histological analyses allowed us to confirm the actual presence of osteomyelitis and demonstrate that clinical differentiation during surgery is effective in identifying a healthy margin.